Human resource management - Ivancevich, John M. (1939-2009); Konopaske, Robert (McGraw-Hill/Irwin, 2013)
Ivancevich and Konopaske takes a managerial orientation; that is it takes the position that HRM is relevant to managers in every unit, project, or team. Managers are constantly faced with HRM issues, problems, and decision-making and the text's primary goal is to show how each manager must be a human resource problem solver and diagnostician. This book pays attention to the application of HRM approaches in "real" organizational settings and situations. Realism, understanding, and critical thinking were important in the revision. Students and faculty alike have identified readability and relevance as key strengths of the text. The Twelfth Edition provides a book that stimulates ideas and keeps all users up-to-date on HRM thinking and practice.